2021
DOI: 10.1007/s12026-021-09226-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of humoral and cellular immunity induced by the BNT162b2 SARS-CoV-2 vaccine in healthcare workers, elderly people, and immunosuppressed patients with autoimmune disease

Abstract: The development of vaccines to prevent SARS-CoV-2 infection has mainly relied on the induction of neutralizing antibodies (nAbs) to the Spike protein of SARS-CoV-2, but there is growing evidence that T cell immune response can contribute to protection as well. In this study, an anti-receptor binding domain (RBD) antibody assay and an INFγ-release assay (IGRA) were used to detect humoral and cellular responses to the Pfizer-BioNTech BNT162b2 vaccine in three separate cohorts of COVID-19-naïve patients: 108 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…The main limitations of the study are that we have not followed up on patients, most patients are still admitted to the ICU, and the short recruitment time of the study. Determination of antibody levels is not part of a routine procedure in hospitalized patients and therefore was not available in a small part of the sample, and we have also been able to observe that having adequate levels does not always ensure not developing the disease, considering the importance that other immunological mechanisms such as cellular immunity occupy in the pathophysiology of this disease [17]. We observed that the first dose of vaccination does not prevent the development of severe forms of the disease, supporting to maximize vaccine uptake with two doses among vulnerable populations.…”
Section: Discussionmentioning
confidence: 97%
“…The main limitations of the study are that we have not followed up on patients, most patients are still admitted to the ICU, and the short recruitment time of the study. Determination of antibody levels is not part of a routine procedure in hospitalized patients and therefore was not available in a small part of the sample, and we have also been able to observe that having adequate levels does not always ensure not developing the disease, considering the importance that other immunological mechanisms such as cellular immunity occupy in the pathophysiology of this disease [17]. We observed that the first dose of vaccination does not prevent the development of severe forms of the disease, supporting to maximize vaccine uptake with two doses among vulnerable populations.…”
Section: Discussionmentioning
confidence: 97%
“…Data on specific anti-Spike (S) antibody production and their protective role in vaccinated subjects are accumulating, while little is known on the T-cell response after vaccination, especially in immunosuppressed subjects ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some attempts have been made in this direction, also considering evaluating IFN-γ using IGRA tests [ 17 ]. However, the T cells’ response is expressed through different activation pathways, and the evaluation of a single cytokine may not fully reflect the state of activation of this compartment.…”
Section: Discussionmentioning
confidence: 99%